Development of the Urban Mobility of Medellín, Colombia, an Example for Costa Rica - Montenegro-Méndez, Marcos Antonio (2019)
Urban mobility is an inherent factor in daily life, its development allows better life conditions and its forget brings an imminent collapse of the city. Today, San José in Costa Rica, is in a time of urgent intervention, the proposed mobility solutions; metro, tram and rapid train are competing between it selves and shows the state of development little planned of the city. Medellín in Colombia is taken as a model that currently has an integrated system of transportation and urban mobility by metro, tram, metrocables (cable railway), metroplús (articulated bus), feeding and integrating systems, to serve as an example to San José. Its development not only distinguish the transportation ways, but also the space and accessibility adequacy that is translated to a better use and appropriation, getting a better life quality for every person who is involve in those services. Through this field investigation done with interviews and bibliography research, its pursuit to orientate a solution to San José’s problematic situation, using such as example the interesting case of development in urban mobility that represents Medellín. Its concluded with this text that solutions to San José’s situation must be generated starting the ideal of integration, also Medellín is an appropriate example and potential source of advice for Costa Rica’s efforts.